Sequential CT Findings in Two Cases of Immunoglobulin G4-Related Lung Disease: Focused on Disease Progression - Dong-Kyu Lee; Soo-Youn Ham (대한영상의학회지, 2018)
Immunoglobulin G4 (IgG4)-related lung disease has been actively studied over the past few years. Radiologic findings of IgG4-related lung disease vary among patients, but there are no long-term follow up studies regarding variations in imaging features over the course of disease progression. In two cases with relatively long-term follow up, diverse early and late computed tomography (CT) findings of IgG4-related lung disease are reviewed in this report. In contrast to nodular or diffuse ground-glass opacity, which was predominantly noted in CT scans at earlier stages of disease, honeycombing and traction bronchiectasis were regarded as late radiologic manifestations. Solid nodules might be visible in both early and late stages; however, development of new solid nodules and enlargement of preexisting nodules could occur during disease progression. Interlobular septal thickening and mediastinal/hilar lymphadenopathy were persistent, even in later stages of the disease. These findings might be useful in making an accurate and timely diagnosis of IgG4-related lung disease.